Pengaruh Jumlah Produk, Pendapatan, Dan Biaya Operasional Terhadap Laba Pada PT Pos Indonesia (Persero) Cabang Jongke Surakarta Periode 2019-2021 - Annisaa Miftakhul Jannah; LMS Kristiyanti; Rukmini Rukmini (Jurnal Akuntansi dan Pajak, 2022)
The purpose of this study was to determine the effect of product, revenue and operating costs on profits at PT. Pos Indonesia (Persero) Jongke Surakarta Branch for the 2019-2021 period, either simultaneously or partially. In this study, the researcher used sekunder data with descriptive analysis method, classical assumption test (normality test, heteroscedasticity test, multicollinearity test, autocorrelation test) and hypothesis testing using multiple linear regression analysis, F test, t test, and R² test. Based on the results of product research, income and operating costs on profit, it is obtained that f count = 30,744 > f table = 2.96, with a significance of 0.000 0.05, so that there is no positive and significant effect of Product on Profit at PT. Pos Indonesia (Persero) Surakarta Jongke Branch for the period 2019-2021. Based on income research on earnings, the results obtained tcount = 8.590 > ttable = 2.055, with a significance of t 0.000